Design and Development of an iOS Application for Early Detection and Monitoring of Scoliosis Using Core Motion - Isviandhy, Gwynneth; Paramita, Adi Suryaputra (Journal of Applied Informatics and Computing, 2025)
Scoliosis is a disorder of the spine characterized by an abnormal curvature in the back, which can impair quality of life if not properly addressed. Early detection is crucial in preventing the worsening of this condition. This research aims to design an iOS-based application to help users independently track the progression of scoliosis. The application employs Core Motion technology to detect and monitor the degree of spinal curvature. Core Motion technology utilizes a gyroscope to implement a digital scoliometer, enabling the measurement of elevation differences between the right and left sides of the body while bending forward, similar to conventional scoliometer. Testing results indicate that the use of these technologies provides fairly accurate and consistent measurements with an accuracy rate reaching 90%. The application is expected to serve as an efficient monitoring tool and a data source in efforts to analyze public health and formulate more effective health policies.